Pengaruh Katekisasi Sidi dan Keteladanan Orang Tua Terhadap Karakter Remaja Kristen di HKBP Paranginan Ressort Paranginan - Simon Petrus Lumbantoruan; Lasmaria Lumban Tobing (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2025)
The purpose of this study was to determine 1) the influence of catechism on the character of Christian adolescents in HKBP Paranginan; 2) the influence of parental role models on the character of Christian adolescents in HKBP Paranginan; and 3) the influence of catechism and parental role models together on the character of Christian adolescents in HKBP Paranginan. The method used in this study is a quantitative method with a descriptive approach. The population was all participants of catechism in HKBP Paranginan totaling 44 people and a sample of 39 people was determined using the Slovin formula. The instrument trial was conducted on 30 adolescents in HKBP Pearung so that it was known that all research instruments were declared valid and reliable because they had met the criteria for validity and reliability values. Data were collected using a closed questionnaire of 35 items. The results of data analysis showed that: 1) the Fcount value> Ftable, namely 12.626> 3.23, thus it is known that there is an influence of catechism on the character of Christian adolescents in HKBP Resort Paranginan partially. The influence is 25.4%, 2) the Fcount value > Ftable is 14.014 > 3.23, thus it is known that the influence of parental role models on the character of Christian teenagers at HKBP Resort Paranginan is partial. The influence is 27.5%, and 3) the Fcount value > Ftable is 12.683 > 3.23, thus it is known that there is an influence of catechism and parental role models simultaneously on the character of Christian teenagers at HKBP Resort Paranginan. The influence is 41.3%, thus Ha is accepted and H0 is rejected.